Trans-translation exposed: understanding the structures and functions of tmRNA-SmpB - GIUDICE, Emmanuel; MACE, Kevin; GILLET, Reynald (Frontiers in Microbiology, 2014)
Ribosome stalling is a serious issue for cell survival. In bacteria, the primary rescue system is trans-translation, performed by tmRNA and its protein partner small protein B (SmpB). Since its discovery almost 20 years ago, biochemical, genetic, and structural studies have paved the way to a better understanding of how this sophisticated process takes place at the cellular and molecular levels. Here we describe the molecular details of trans-translation, with special mention of recent cryo-electron microscopy and crystal structures that have helped explain how the huge tmRNA-SmpB complex targets and delivers stalled ribosomes without interfering with canonical translation.